ANALISIS FAKTOR PENENTU LABA DALAM PERHITUNGAN HARGA POKOK PENJUALAN DI RESTORAN KEMBANG GOELA, PT NUSANTARA BOGA ABADI, JAKARTA SELATAN. - Oktaviani, Riri; Krisanti, Imelda; Gustiyanti, Ferra; Sukardi, Sukardi; Herawati, Tuti; Saksana, Joned C; Hidayatullah, Syarif (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2023)
This research aims to analyze the implementation and acquisition of sales and cost of goods sold on food menus at PT Nusantara Boga Abadi to calculate net sales profit. This research serves as a benchmark to determine whether the profit margin obtained by the company is optimal. The data used are secondary data in the form of raw material purchases. The method used is descriptive analysis with a quantitative approach. PT Nusantara Boga Abadi operates in the food industry, and the focus of this research is "how to determine the final cost of goods sold at the Kembang Goela Restaurant." This research employs field and library research methods. Data collection is conducted through observation, interviews with stakeholders, documentation, and literature studies. The collected data is then analyzed using the Full Costing method to determine the cost of production, which subsequently serves as the basis for setting the selling price. The analysis results indicate that the application of the Full Costing method in determining the cost of production yields favorable outcomes, enabling profit increase by accounting for all cost elements. The findings of this research are expected to provide valuable insights for the management of Kembang Goela Restaurant to enhance profitability and maintain business sustainability.